Aging, sexuality and nursing care: the elderly woman’s look - Cinoélia Leal de Souza; Vanda Santana Gomes; Roberta Lopes da Silva; Elaine Santos da Silva; Jaqueline Pereira Alves; Núbia Rêgo Santos; Victor Neves Reis; Simone Aline Ferreira (Revista Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to analyze the perception of elderly women about sexuality and practice of nursing care in this context. Method: a descriptive qualitative study. Fifty elderly women from Guanambi City - Bahia State were interviewed in 2016. Data collection technique was direct interview by using an unstructured script. Analysis of the semantic content described was carried out, and two empirical categories: the elderly woman’s view of nursing care in the promotion of sexual health and experience of sexuality in the elderly; and nursing care in the context of women’s aging. Results: it has been noted that the elderly women are afraid to talk about sexuality, especially with health professionals. By influences of society, they often exclude this issue of health care for elderly women. Final considerations: changes must be thought about assistance provided in relation to sexuality.